2021
DOI: 10.3390/jcm10173820
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Clinical and Laboratory Criteria for Diagnosing Autoimmune Liver Disease among Patients with Systemic Lupus Erythematosus: An Observational Study

Abstract: Abnormal liver function tests are frequently observed during follow-up of patients with systemic lupus erythematosus (SLE) but data on co-existence with autoimmune liver diseases (AILD) are scarce. This retrospective study aimed to describe the prevalence of autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC) among well-characterized subjects with SLE. We also evaluated whether the presence of autoantibodies to complement protein 1q (C1q) and/or ribosomal P protein (anti-ribP) are, directly or inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Notably, although AILD like AIH and PBC are considered rare, their coexistence with SLE in patients presenting with liver enzyme abnormalities is relatively common [61]. The overlap rates of SLE with AIH and PBC were 1.6-15% and 2.2-7.5%, respectively [62,63]. Current MR results support a genetically predicted causal relationship between SLE and PBC.…”
Section: Discussionmentioning
confidence: 59%
“…Notably, although AILD like AIH and PBC are considered rare, their coexistence with SLE in patients presenting with liver enzyme abnormalities is relatively common [61]. The overlap rates of SLE with AIH and PBC were 1.6-15% and 2.2-7.5%, respectively [62,63]. Current MR results support a genetically predicted causal relationship between SLE and PBC.…”
Section: Discussionmentioning
confidence: 59%
“…In addition, we did not perform functional assays, like cytokine, granzyme, and perforin analyses, which could have provided us with important insights about the activity of CD4 and CD8 T cells. Finally, a previous study has shown that Systemic Lupus Erythematosus (SLE) and AIH can reach 14% of similarity in their pathogenesis, 30 an overlap that has been described in pediatric patients. 32 It is speculated that DNA and RNA release by apoptotic cells in patients with SLE are potent stimuli to pDCs, via TLR-7 and -9 activation and high IFN-I production.…”
Section: Discussionmentioning
confidence: 93%
“…29 Even Treg cells present in the inflamed hepatic tissue, which apparently have normal activity, may be involved in the AIH pathogenesis due to characteristics of the hepatic milieu, such as deficiency of IL-2, an essential cytokine for Treg function. 30 In the context of treated AIH, normal peripheral Treg cell rates could be a consequence of the immunosuppressive therapy, which, among other mechanisms, decreases the activity of selfreactive T and B cells and boost the activity of Treg cells. 31 Our study has a number of limitations, including its cross-sectional design and a small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…By genome-wide studies, both diseases have been reported to share the IRF5-TNPO3 gene-spanning haplotype loci[ 65 ]. The prevalence of PBC in SLE patients with liver dysfunction ranges from 2.2% to 7.5%, usually lower than that of AIH[ 39 , 53 - 55 , 57 ]. In a review of SLE overlapping with PBC, 69% were diagnosed first by PBC, 24% had coexisting SS, and 2 deaths were due to PBC-related hepatic failure[ 66 ].…”
Section: Slementioning
confidence: 99%